2019
DOI: 10.3390/su11184838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors Affecting Firms’ Financial Performance—Support for Managerial Decision-Making

Abstract: This paper aims to investigate how financial variables and exogenous crises influence firms’ financial performance, and how these factors may help managers in decision-making to increase their firm’s wealth. The dynamic interactions among variables were studied by applying a panel vector autoregressive model using annual data for a sample of non-financial firms from European countries. Results indicate that liquidity, leverage and productivity positively affect firm performance, while solvency and asset turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
(62 reference statements)
7
22
0
Order By: Relevance
“…The importance of this indicator is mainly to gauge the efficiency of a company's operational management (Neves et al , 2020a) to perceive the degree of compliance with short-term obligations, for better performance. Companies that obtain greater liquidity reduce their financing costs, increasing, in turn, profitability (Barbuţă-Mişu et al , 2019).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The importance of this indicator is mainly to gauge the efficiency of a company's operational management (Neves et al , 2020a) to perceive the degree of compliance with short-term obligations, for better performance. Companies that obtain greater liquidity reduce their financing costs, increasing, in turn, profitability (Barbuţă-Mişu et al , 2019).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Both operating and financial leverages take into account objective factors that affect the potential for profit. But, in addition to objective factors, there are also subjective factors that also have a significant impact on the potential business profitability (Bărbută-Misu et al, 2019). The key subjective factor in making strategic decisions is the financial mentality of the company's owners and / or managers.…”
Section: Problem Statementmentioning
confidence: 99%
“…Other study (Saleem and Rehman, 2011) [10], applied a linear regression model to determine the correlation between the liquidity and profitability indicator, and the empirical results of the study confirmed that there exist an important control of liquid ratio on ROA whereas there is an insignificant effect on ROE indicator. In his study, (Bărbuță-Mișu et al, 2019) [3] analyse what are the possible factors able to influence the financial performance level, in firms of the European Union, given the crisis period effect. They presented the risk factors capable to affect asset values and firms' financial performance, but in the paper, they have been highlighting the following factors: borrowed capital repayment and labour productivity, leverage, solvency, asset turnover, liquidity as representing indicators that are affected by a potential financial crisis.…”
Section: Problem Statementmentioning
confidence: 99%
“…Digi Communications Group is a leading European operator in the field of electronic communications, with operations in Romania, Hungary, Spain and Italy. Depending on the number of fixed internet connections registered at the end of 2019, in Romania, Digi had a market share of 53%, Telekom Group 21%, the other providers totalling 26% 3 .…”
Section: Introductionmentioning
confidence: 99%